2011
DOI: 10.1007/s00125-011-2226-1
|View full text |Cite
|
Sign up to set email alerts
|

Wld S protects against peripheral neuropathy and retinopathy in an experimental model of diabetes in mice

Abstract: Aims/hypothesis We aimed to evaluate the effect of the mutant Wld S (slow Wallerian degeneration; also known as Wld) gene in experimental diabetes on early experimental peripheral diabetic neuropathy and diabetic retinopathy.Methods The experiments were performed in four groups of mice: wild-type (WT), streptozotocin (STZ)-induced diabetic WT, C57BL/Wld S and STZ-induced diabetic C57BL/Wld S . In each group, intraperitoneal glucose and insulin tolerance tests were performed; blood glucose, glycated haemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
(45 reference statements)
0
20
3
Order By: Relevance
“…Previous investigations conducted in our laboratory have placed SR-A in the center of this process (46,48,50). Our new data suggest that SR-A suppresses RAGE-induced M1 polarization by inhibiting MKK7-dependent JNK activation.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Previous investigations conducted in our laboratory have placed SR-A in the center of this process (46,48,50). Our new data suggest that SR-A suppresses RAGE-induced M1 polarization by inhibiting MKK7-dependent JNK activation.…”
Section: Discussionmentioning
confidence: 50%
“…Recent investigations by our laboratory and others have made a strong case for SR-A-mediated macrophage polarization in the pathogenesis of myocardial infarction (20), stroke (46), lung carcinogenesis (5), insulin resistance (51), and diabetic nephropathy (50). Of note, SR-A deletion exerts distinct effects on stress-induced organ injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It attenuates the axon degeneration that is associated with several neurodegenerative disease models (13,18,19,36,38). In our previous study, we have shown that Wld S could attenuate experimental diabetes and early experimental peripheral diabetic neuropathy and diabetic retinopathy (52). Here, we wanted to determine whether the Wld S gene plays a renoprotective role during the progression of diabetic renal injury.…”
Section: Wldmentioning
confidence: 99%